The Influence of Emotional Intelligence on Learning Discipline of Class V SD Students State 066049 Medan Helvetia - Asa'aro Laia, Robinson Hutagaol, Winny Sunfriska Limbong, Wahyu Indah Lestari (Education Achievement: Journal of Science and Research, 2021)
The aim of this research is to determine the influence of emotional intelligence on the discipline of class V students at SD Negeri 066049 Medan Helvetia. This type of research is quantitative research. The method used in this research uses survey research methods. The population in this study was class V students at SD NEGERI 066049 Medan Helvetia, totaling 24 students. and all students were sampled using a saturated sampling technique. The analytical method used in this research is the prerequisite analysis test, namely the normality test, linearity test and hypothesis test using a simple linear regression test. The researcher carried out a hypothesis test using a simple linear regression analysis technique using SPSS 25, so the calculated t value was 32.381 and the t table value was obtained. which has been determined in the statistical table with a significance of 0.05 with df = 24 - 2 = 22 of 2.073. So it means that the calculated t value is 32.381 t > table 2.073 then????0 rejected and???????? accepted, which means that emotional intelligence can influence the learning discipline of class V students at SD Negeri 066049. Based on the results of research and discussion, it shows that emotional intelligence has a positive and significant effect on the learning discipline of class V students at SD Negeri 066049 Medan Helvetia. This means that the higher the emotional intelligence, the higher the student's learning discipline.